Hubungan Implementasi Patient Safety Di Unit Pelayanan Bedah Terhadap Kepuasan Pasien di RST Wijayakusuma Purwokerto - Farahdila, Ananda; Yulistiani, Mustiah (Jurnal Keperawatan Muhammadiyah, 2025)
Background: The quality of safety and security in the operating room, integrated with the surgical ward, is a key indicator of the improvement of healthcare services worldwide. Patient satisfaction is one of the indicators used to assess the quality of care in hospitals. The quality of healthcare services refers to the extent to which these services meet the expectations of patients. Higher levels of patient satisfaction reflect better healthcare quality. Objective: To determine whether there is a relationship between the implementation of Patient Safety in the surgical service unit and patient satisfaction at RST (Military Hospital) Wijayakusuma Purwokerto. Methods: This quantitative research utilized a descriptive-analytical approach with a cross-sectional design. Sampling was conducted using Non-Probability Sampling with Purposive Sampling based on inclusion and exclusion criteria, resulting in a sample size of 51 respondents. The analysis employed Chi-Square testing. Results: Bivariate analysis using Chi-Square testing yielded a p-value of 0.002, which is less than 0.05. This indicates a significant correlation between the implementation of patient safety in the surgical service unit and patient satisfaction at RST Wijayakusuma Purwokerto. Conclusion: There is a significant correlation between the implementation of patient safety in the surgical service unit and patient satisfaction at RST Wijayakusuma Purwokerto.